The Incidence and Prediction of Self-Injury Among Sentenced Prisoners - Martin, Michael S (The Canadian Psychiatric Association, 2014)
OBJECTIVE: Prevention of self-injurious behaviour is an important priority in correctional settings given higher rates among inmates. Our study estimated the reported incidence of self-injury during the first 180 days in prison and tested potential risk and protective factors using official prison records. METHODS: We conducted a retrospective cohort study using secondary data for 5154 admissions to the Correctional Service of Canada during 2011. Relative risks were estimated with Poisson regression. Recursive partitioning was used to create a parsimonious model of characteristics of offenders who engage in self-injury. RESULTS: Thirty-six of 5154 (0.7%) offenders engaged in 1 or more incidents of self-injury during their first 180 days of incarceration. Educational and occupational achievement, family history, demographic factors, mental health service use, and results of mental health screening at intake were predictive of self-injury. Recursive partitioning models identified about 23% of inmates who presented with multiple risk factors, and had increased incidence of self-injury. A comparison of a model using information at intake to a model also incorporating events in prison suggested that events in prison added little to the detection of self-injury. CONCLUSIONS: Given high rates of most risk factors, screening for self-injury during early incarceration will be overinclusive. However, it may identify a group of inmates with complex needs for whom interdisciplinary responses are needed to address wide-ranging social, family, behavioural, and mental health deficits.